On Teaching Visually Impaired Students in Russian Educational Institutions of Music - Gorbunova, Irina B.; Morozov, Sergey A. (The journal of contemporary issues in business and government, 2021)
Purpose of the study: This study discusses questions associated with the creation and development of new techniques of teaching music people with visual impairments, rethinking the methods of teaching traditional disciplines in the education system which is based on introduction of music computer technologies (MCT). The question is raised about the need to develop specialized software for the blind in order to optimize the process of their musical education. Methodology: In this work, we investigated the content aspects of the methodology of teaching musical disciplines with using MCT for music students with deep visual impairments: the content and methodological support for teaching these disciplines were developed, and methodological approaches for implementing the educational process in the practice of teaching visually impaired music students in secondary and higher educational institutions were determined. Main findings: It was found that the study of the disciplines "Computer Arrangement" and "Musical Informatics" based on using MCT is of the greatest importance for the growth of professional competencies and social adaptation of music students with profound visual impairments. The thematic range and content of these disciplines is very diverse, which allows you to form stable orientation skills in a high-tech information educational environment and helps to overcome professional and socially significant difficulties. Applications of this study: The research findings can be of interest for musicians with profound visual impairments, blind students and their teachers, and for specialists dealing with problems of socialization and social adaptation of people having vision limitations. Novelty/Originality of this study: The development of MCT contributes to the integration of visually impaired musicians into the professional community. A set of academic disciplines has been developed based on the use of MCT, which is implemented in the process of professional training of music students with deep visual impairments in a number of educational institutions in Russia. The international community and the state should more actively support and develop technologies that promote the socialization and professional adaptation of visually impaired musicians.